2021
DOI: 10.1177/03635465211015682
|View full text |Cite
|
Sign up to set email alerts
|

High Rate of Initially Overlooked Kaplan Fiber Complex Injuries in Patients With Isolated Anterior Cruciate Ligament Injury

Abstract: Background: Injuries to the Kaplan fiber complex (KFC) are not routinely assessed for in the anterior cruciate ligament (ACL)-deficient knee during preoperative magnetic resonance imaging (MRI). As injuries to the KFC lead to anterolateral rotatory instability (ALRI) in the ACL-deficient knee, preoperative detection of these injuries on MRI scans may help surgeons to individualize treatment and improve outcomes, as well as to reduce failure rates. Purpose: To retrospectively determine the rate of initially ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 31 publications
2
22
0
Order By: Relevance
“…In the present study by Berthold et al, 5 the only associated radiographic marker with a statistically significant correlation suggestive of KFC injury was bleeding in the lateral femoral supracondylar region. The authors once again reference the proximity of the superior genicular artery to the KFC, which is valid.…”
Section: Dear Editorsupporting
confidence: 43%
See 3 more Smart Citations
“…In the present study by Berthold et al, 5 the only associated radiographic marker with a statistically significant correlation suggestive of KFC injury was bleeding in the lateral femoral supracondylar region. The authors once again reference the proximity of the superior genicular artery to the KFC, which is valid.…”
Section: Dear Editorsupporting
confidence: 43%
“…Importantly, an association between radiological KF injury and increased anterolateral rotatory laxity or higher rates of ACL reconstruction (ACLR) failure has not been shown in any clinical series. 1,8 In the current study by Berthold et al, 5 a high prevalence of injury to the Kaplan Fiber Complex (KFC) (either proximal, distal, or both fibers) was reported, varying between 35.6% and 53.8% among different raters. The study concluded that, ''KF integrity and injury can be reliably detected on routine knee MRI.''…”
Section: Dear Editormentioning
confidence: 49%
See 2 more Smart Citations
“…As such, we believe that improvement in preoperative diagnosis, such as implementing 3-dimensional T1- and T2-weighted turbo spin echo sequences, 6 which could be included in routine protocols, may be helpful in assisting the surgeon’s choice if an additional LET should be discussed. 5 Finally, as correctly stated by Drs Devitt and Batty, bleeding or edema in this region may not be pathognomy for KFC injuries; however, if present, the surgeon should maintain special awareness for injuries in the anterolateral complex.…”
mentioning
confidence: 94%